NATO Enlargement and Security in the Balkans - Zagorcheva, Dessie (Journal of Regional Security, 2012)
This article examines the impact of NATO enlargement on security and democratization in East Central Europe in order to draw lessons for aspirants in the Western Balkans. I analyze some of the main arguments of Neo-realists and Neo-liberal Institutionalists on the role of international institutions like the EU and NATO for increasing stability and security, and for fostering cooperation among states. While neither theory wins, the article finds evidence to support some of the main propositions of both the Realist and the Institutionalist schools of thought. The theoretical analysis is then used to draw policy recommendations about the continuing enlargement of NATO and the Euro-Atlantic perspective for the Western Balkan states.